Changes in HTO and OBT activity concentrations in the Perch Lake aquatic ecosystem. (December 2016) - Kim, S.B.; Farrow, F.; Bredlaw, M.; Stuart, M.
Abstract: Perch Lake, a small shallow shield lake located on the Chalk River Laboratories (CRL) site, contains elevated levels of tritium due to inputs from a nearby nuclear waste management area. The releases have been going on for many years but tritium levels in Perch Lake have been gradually decreasing since about year 2000. Lake water, sediments, aquatic plants, clams and fish were collected during the summer and fall of 2003 and 2013 at three locations in the lake. HTO activity concentrations were measured in all samples and OBT activity concentrations were measured in sediments, plants, clams and fish. In 2003, 2013, HTO activity concentrations in lake water were roughly uniform in time and space, except close to the shoreline where concentrations were fluctuating according to stream water and groundwater tritium levels in streams entering the lake. HTO activity concentrations of biota were similar to concentrations in lake water at the site where they were collected. OBT activity concentrations in biota were not always correlating with the lake water HTO levels. OBT to HTO ratios were found to be less than 1 for aquatic plants, around 1 for clams and fish and above 1 for birds reared on the shore of the lake. Highlights: HTO and OBT concentrations of lake water, sediments, aquatic plants, clams, fish and bird in Perch Lake were determined. HTO concentrations of biota were similar to concentrations in lake water at the site where they were collected. OBT concentrations in biota showed little variation in time or space in 2013 but showed much greater variability in 2003.